2015
DOI: 10.1061/(asce)cc.1943-5614.0000553
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Modeling of Masonry-Infilled RC Frames Retrofitted with Textile-Reinforced Mortar

Abstract: Abstract:The present paper proposes an analytical approach for modeling the behavior of textilereinforced mortar (TRM)-strengthened masonry-infilled reinforced concrete (RC) frames under seismic loading. The model falls into the discrete diagonal-element type and is based on the use of single-strut and single-tie elements to represent the infill panel. It builds on the results of past experimental studies by the authors in which the application of TRM jacketing was proved to be effective for the seismic retrof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…In this part of the paper some details of the experimental case study regarding the masonry-infilled RC frame with the strengthening material TRM are presented for the benefit of the reader. Full details about the experimental case study can be found in Koutas et al [32] [33].…”
Section: Description Of Experimental Case Studymentioning
confidence: 99%
See 2 more Smart Citations
“…In this part of the paper some details of the experimental case study regarding the masonry-infilled RC frame with the strengthening material TRM are presented for the benefit of the reader. Full details about the experimental case study can be found in Koutas et al [32] [33].…”
Section: Description Of Experimental Case Studymentioning
confidence: 99%
“…(a) (b) Figure 3 : (a) Test set up [33] and (b) Imposed cyclic deformation history for all stories [33].…”
Section: Experimental Campaignmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13] has allowed a qualitative leap in the field. In this case, simple FEM models will be developed in order to create a model to be use it in large structural models of complete constructions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in an attempt to avoid problems associated with the use of epoxy resins, an innovative composite material, known as Textile Reinforced Mortar (TRM), was developed (Papanicolaou et al, 2008). TRM has been used over the last decade for seismic retrofitting of structures, particularly concrete and masonry structures (Bousias et al, 2007;Koutas et al, 2014;Koutas et al, 2015;Tetta et al, 2015). While studies have shown that TRMs are more effective in increasing the deformation capacity of structures, they are generally less effective in resisting shear compared to FRP (Tetta et al, 2015).…”
Section: Introductionmentioning
confidence: 99%